A ATUAÇÃO DO PROFISSIONAL DE GEOLOGIA NAS OPERAÇÕES DE DESASTRE – ASPECTOS LEGAIS - Aline Freitas da Silva, Rodolfo Moreda Mendes, Alexandre Moura Coelho e Francisco Dourado (Revista Eletrônica da OAB-RJ, 2025)
O Brasil é um país suscetível a diversas tipologias de ameaças associadas a desastres geológicos. O número de ocorrências, de vítimas fatais e pessoas afetadas, além dos valores de danos e prejuízos expõe a importância e a gravidade da questão e deixa claro a necessidade do profissional de geologia nas ações de Gestão de Risco e do Gerenciamento do Desastre, incluindo a etapa de Resposta. Contudo existe uma lacuna no arcabouço legal que desampara a atuação deste profissional em situações de desastre, pois a lei que regulamenta a profissão data da década de 1960, não previu esta situação e pouco se avançou desde então. Este trabalho tem por objetivo a discussão acerca deste tema. Entende-se que esta vulnerabilidade afeta a capacidade de resposta prestada pelos profissionais de geologia durante um desastre e por consequência, as instituições onde eles atuam. Por esta razão faz-se necessária a ampliação do debate de forma a encorajar uma maior participação dos profissionais na construção de instrumentos normativos protetivos à atuação do especialista técnico de geologia nas operações durante um desastre. Abstract Brazil is a country susceptible to various types of hazards associated with geological disasters. The number of occurrences, of fatalities and people affected, in addition to the amounts of damage and losses, exposes the importance and gravity of the issue and makes clear the need for the geology professional in the actions of Risk Management and Disaster Management, including the response stage. However, there is a gap in the legal framework that prevents this professional from acting in disaster situations, because the law that regulates the profession dates from the 1960s, did not foresee this situation and little progress has been made since then. This paper aims to discuss this theme. It is understood that this vulnerability affects the response capacity provided by geology professionals during a disaster and, consequently, the institutions where they work. For this reason, it is necessary to expand the debate in order to encourage greater participation of professionals in the construction of normative where they work. For this reason, it is necessary to expand the debate in order to encourage greater participation of professionals in the construction of normative instruments that protect the role of the technical specialist of geology in disaster operations.